Collaboration of Tangerang City Government in Waste Management through Waste Bank - Erfanti, Marlinda; Nurliah Nurdin; Asropi (Journal of Public Administration and Government, 2024)
This study aims to examine the collaboration undertaken by the Tangerang City Government in waste management through waste banks. The waste problem in Tangerang City is evident from the annual increase in waste production. This is reflected in the significant volume of waste disposed of at the Rawa Kucing landfillin Neglasari District, which reached 494,176,281.08 tons/year in 2021. As of 2024, the volume of waste sent to the landfill has reached 412,514,564.64 tons/year (data as of September 6, 2023). The Tangerang City Government has collaborated with several waste banks in different areas to manage inorganic waste. The actors involved in this collaboration include the Tangerang City Government, represented by the Environmental Agency, which acts as the leader and initiator of the collaboration for waste management through waste banks. In accordance with Regional Regulation No. 02 of 2021, the government is obligated to establish a central waste bank as a coordinator and facilitator linking the Tangerang City Government with unit waste banks. This research adopts a qualitative method and employs the theory of Emerson and Nabatchi (2015), which posits that local governments are not the sole primary actors initiating collaboration. Furthermore, collaborative governance is understood as the process, structure, and implementation of policies involving government institutions, the private sector, and the community to meet public needs and interests. Field research revealedseveral challenges in collaboration, including procedural and institutional arrangements, leadership, knowledge, and resources.